Intracardiac biopsy of cardiac tumors with echocardiographic guidance: Case report - Jinyun Zhu; Ning Zhang; Qunchao Ma; Luhang Jin; Xiaohong Pan (Frontiers in Cardiovascular Medicine, 2023)
BackgroundPrimary cardiac tumors are very rare, and about 20–30% of them are malignant tumors. Since early signs of cardiac tumors are non-specific, diagnosis can be challenging. There is a lack of the recommended guidelines or standardized strategies for diagnosis and optimal treatment for this disease. As the definite diagnoses of most tumors are made by pathologic confirmation, biopsied tissue is essential in determining the treatment for patients with cardiac tumors. Recently, intracardiac echocardiography (ICE) has been introduced to assist biopsy procedures of cardiac tumors and it provides high-quality imaging.Case DescriptionDue to its low prevalence and variable presentation, cardiac malignant tumors usually are easily missed. Hereby, we report three cases of patients who presented with non-specific signs of cardiac disorder and was initially suspended diagnosis as lung infection or cancer. Under the guidance of ICE, cardiac biopsies were successfully on cardiac masses, giving critical data for diagnosis and treatment planning. No procedural complications were obtained in our cases. These cases are intended to highlight the clinical value and importance of ICE-guided biopsy of intracardiac mass.ConclusionsThe diagnosis of primary cardiac tumors relies on the histopathological results. In our experience, using ICE for biopsy of an intracardiac mass is an attractive tool to increase diagnostic results and reduce the risk of cardiac complications associated with inadequate targeting of the biopsy catheters.